2022
DOI: 10.4103/aja.aja_40_21
|View full text |Cite
|
Sign up to set email alerts
|

Low-intensity extracorporeal shock wave therapy for Peyronie's disease

Abstract: The aim of this article is to assess the outcomes of a low-intensity extracorporeal shock wave therapy (LiESWT) protocol for the treatment of Peyronie's disease (PD). Patients treated for PD were prospectively recorded, and data were retrospectively reviewed. Age, characteristics of fibrous plaques, concomitant treatments, International Index of Erectile Function (IIEF-5), Lue score, and pain score on Likert scale were collected. Patients in acute phase of PD and an angulation of <40° were included. The protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…That said, only 63 patients in the initial study group were available for long‐term evaluation 97 . Available retrospective trials also did not show its efficacy 98,99 …”
Section: Other Non‐invasive Methods Of Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…That said, only 63 patients in the initial study group were available for long‐term evaluation 97 . Available retrospective trials also did not show its efficacy 98,99 …”
Section: Other Non‐invasive Methods Of Treatmentmentioning
confidence: 99%
“…97 Available retrospective trials also did not show its efficacy. 98,99 In comparison with other conservative treatment methods, ESWT seems to be associated with poor outcomes, and despite a favorable safety profile, there might be limited merit to further research on this subject.…”
Section: Extracorporeal Shockwave Therapymentioning
confidence: 99%
“…The first hypothesis suggests that the shock waves directly damage the penile plaques, leading to penile tissue remodeling, while the second hypothesis suggests that the heat generated by the shock waves causes an inflammatory reaction that leads to increased macrophage activity and subsequent degradation of the plaque. Available studies with extracorporeal shock therapy (Table 1) have shown a reduction in pain in patients with PD [19][20][21][22][23][24][25][26], a reduction in PD [19][20][21]25,26], a reduction in plaque [20,21,25] , improving erectile function (EF) [20,21,23,25], lengthening the penis [21], improving quality of life [23]. Only one clinical study did not observe any significant change after the application of ESWT [27].…”
Section: Introductionmentioning
confidence: 99%